A review on motion planning and obstacle avoidance approaches in dynamic environments - Abid Muslim, Farah Kamil; Tang, Sai Hong; Khaksar, Weria; Zulkifli, Norzima; Ahmad, Siti Azfanizam (OMICS International, 2015)
Path planning with obstacles avoidance in dynamic environments is a crucial issue in robotics. Numerous approaches have been suggested for the navigation of mobile robots with moving obstacles. In this paper, about 80 articles have been reviewed and briefly described to offer an outline of the research progress in motion planning of mobile robot approaches in dynamic environments for the last five years. The benefits and drawbacks of each article are also explained. These papers are classified based on their issues into ten groups which are: smooth path, safety, path length, run time, accuracy, stability, less computation cost, control, efficiency, and future prediction (uncertainties). Finally, some challenging topics are presented based on the papers mentioned.